The effects of sense of meaningfulness and teaching role attributes on work outcomes – using the insight of job characteristics model - Juhdi, Nurita; Abd Hamid, Ahmad Zohdi; Siddiq, Mohd Saeed (Institute of Interdisciplinary Business Research, 2010)
The present study sought to examine the effects of teaching role attributes and sense of meaningfulness to work outcomes. In previous studies that examined the relationship between job attributes and work outcomes, the mediating variable was underrepresented and excluded from the model. Teaching role attributes was measured by combining four major teaching roles (pedagogical, managerial, technical and subject-designing) into an index. The work outcomes examined were internal motivation, job satisfaction and perceived work effectiveness. Sense of meaningfulness was hypothesized as the mediating variable in the relationship between teaching role attributes and the work outcomes. Two hundred and ninety two lecturers teaching in Malaysia tertiary educations were involved in this study. Questionnaires were used to solicit their responses which were distributed using various means; online, personal visits and regular mails. The measurement items were mainly adapted from Job Diagnostic Survey. The results from the findings indicated that sense of meaningfulness mediated the relationships between teaching role attributes and the work outcomes. It showed that to maximize teachers work outcomes, they must experience the sense of meaningfulness in their jobs.